Fluorescence in situ hybridization (FISH) or rDNA genes (5S and 18-5.8-28S) as a tool for chromosomal tagging and to assess the occurrence of somatic and sperm aneuploidy in Pacific oyster Crassostrea gigas - Benabdelmouna, Abdellah; Nadolna, Katarzyna; Ledu, Christophe (XVI Plant & Animal Genome Conference (PAG), 2008)
Aneuploidy (or alteration of chromosome number) has been frequently described in diploid, triploid and tetraploid C. gigas. In diploid Pacific oysters, aneuploidy affects 1 to 3 chromosomes in up to 35% of the somatic cells and is positively correlated with inferior growth of the animal and thus could be associated with significant economic loss in this major aquaculture species. In polyploid Pacific oysters, aneuploidy was shown to be more heavily frequent and is linked to reversion to lower ploidy levels and is at the origin of aberrant gametes formation. In this context, identification of individual chromosomes involved in aneuploidy events both in somatic and germinal cells would be an important step towards the study of the exact occurrence of this phenomenon and would provide means of screening genitors and gametes in order to establish aneuploid-free tetraploid stocks dedicated to breeding programs and/or serving as male genitors in hatchery-based triploid production. For this purpose, Fluorescent in situ hybridization (FISH) of rDNA genes (5S and 18-5.8-28S) onto somatic metaphasic plates was successfully used to tag three out of ten chromosomes. The same probes appear to be also effective when used onto decondensed sperm nuclei. These preliminary results open the way for a reliable and fast study of the aneuploidy in both somatic and sperm cells and further analyses are currently in progress in order to obtain additional chromosomal tags and to accelerate the procedure of aneuploid detection by the mean of PRINS (primed in situ labelling) approach.